Efficacy and safety of rituximab for primary membranous nephropathy with different clinical presentations: a retrospective study - Zhang, Shasha; Huang, Jing; Dong, Jianwei; Li, Zhuo; Sun, Mengyao; Sun, Yujiao; Chen, Bing (Frontiers in Immunology, 2023)
Abstract Background: Rituximab (RTX) is gaining increasing clinical acceptance in the treatment of primary membranous nephropathy (PMN), with demonstrated efficacy and safety. However, there are few clinical studies on RTX for PMN in Asian populations, especially in China. Methods: To observe and analyse the efficacy and safety of RTX treatment, 81 patients with PMN suffering from nephrotic syndrome (NS) were enrolled and divided into an initial therapy group, a conventional immunosuppressive therapy relapse group, and a conventional immunosuppressive therapy ineffective group according to their pre-RTX treatment background. Patients in each group were followed up for 12 months. The primary outcome was clinical remission at 12 months, and the secondary outcomes were safety and the occurrence of adverse events. Results: At 12 months, 65 of 81 (80.2%) patients achieved complete (n=21, 25.9%) or partial (n=44, 54.3%) remission after rituximab treatment. Thirty-two of 36 (88.9%) patients in the initial therapy group, 11 of 12 (91.7%) patients in the relapse group and 22 of 33 (66.7%) patients in the ineffective group achieved clinical remission. All 59 patients with positive anti-PLA2R antibodies showed a decreasing trend in antibody levels after RTX treatment, and 55 (93.2%) of them achieved antibody clearance (<20 U/mL). Logistic regression analysis showed that a high anti-PLA2R antibody titer (OR=0.993, P=0.032) was an independent risk factor for nonremission. Adverse events occurred in 18 (22.2%) patients, of which 5 (6.2%) were serious adverse events, and none were malignant or otherwise fatal. Conclusion: RTX alone can effectively induce remission PMN and maintain stable renal function. It is recommended as the first choice of treatment and is also effective in patients who relapse and have poor responses to conventional immunosuppressive therapy. Anti-PLA2R antibodies can be used as a marker for RTX treatment monitoring, and antibody clearance is necessary to achieve and improve the rates of clinical remission.